2008
DOI: 10.1021/nn700375n
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Solution-Processed Reduced Graphene Oxide Films as Transparent Conductors

Abstract: Processable, single-layered graphene oxide (GO) is an intriguing nanomaterial with tremendous potential for electronic applications. We spin-coated GO thin-films on quartz and characterized their sheet resistance and optical transparency using different reduction treatments. A thermal graphitization procedure was most effective, producing films with sheet resistances as low as 10(2) -10(3) Omega/square with 80% transmittance for 550 nm light. Our experiments demonstrate solution-processed GO films have potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

97
2,189
9
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,010 publications
(2,308 citation statements)
references
References 32 publications
97
2,189
9
13
Order By: Relevance
“…The reduction of GO by pure hydrazine in the solution phase is particularly interesting because it can produce RGO of relative high quality with relatively small oxygen content 18 . Direct reduction of GO film has also been reported by exposure to hydrazine vapour and/or annealing at high temperature [19][20][21][22] . However, these approaches often involve highly toxic chemicals, require long reduction time, or require hightemperature treatment that are incompatible with flexible plastic substrates, and produce RGO with a relatively high oxygen content (B49%) to give rise to high sheet resistance 23 .…”
mentioning
confidence: 92%
“…The reduction of GO by pure hydrazine in the solution phase is particularly interesting because it can produce RGO of relative high quality with relatively small oxygen content 18 . Direct reduction of GO film has also been reported by exposure to hydrazine vapour and/or annealing at high temperature [19][20][21][22] . However, these approaches often involve highly toxic chemicals, require long reduction time, or require hightemperature treatment that are incompatible with flexible plastic substrates, and produce RGO with a relatively high oxygen content (B49%) to give rise to high sheet resistance 23 .…”
mentioning
confidence: 92%
“…The most common technique has been the oxidisation and subsequent exfoliation of graphite to give graphene oxide. [3][4][5][6][7] However, this technique suffers from one significant disadvantage; the oxidisation process results in the formation of structural defects as evidenced by Raman spectroscopy 3,6 . These defects alter the electronic structure of graphene so much as to render it semiconducting 8 .…”
Section: Introductionmentioning
confidence: 99%
“…These defects alter the electronic structure of graphene so much as to render it semiconducting 8 . These defects are virtually impossible to remove completely; even after annealing at 1000 o C, residual C=O and C-O bonds are observed by X-ray photoelectron spectroscopy 7 . Even mild chemical treatments, involving soaking in oleum, result in non-negligable oxidisation which requires annealing at 800 o C to remove 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the transfer of graphene film, the film‐formation of GO demonstrates to be more convenient and scale‐up, as well as no limit to substrates. Numerous approaches have been adopted to prepare GO films, including drop‐casting,52, 53 spin‐coating,54 vacuum filtration,5, 55 or other assembly processes56, 57, 58, 59 and so on.…”
Section: Properties and Preparationmentioning
confidence: 99%
“…Chen and Bao et al spin‐coated GO dispersions on the prepared substrate and controlled its thickness by adjusting the rotating speed 54. With low rotating speed to uniformly spread and high speed to a thin layer, they found that the single‐layered graphene films shown sheet resistances as low as ≈10 2 –10 3 Ω sq –1 and with 80% transmittance for 550 nm light.…”
Section: Properties and Preparationmentioning
confidence: 99%